Univalence Criteria and Lipschitz-Type Spaces on Pluriharmonic Mappings - Chen, Sh.; Ponnusamy, S.; Wang, X. (MATHEMATICA SCANDINAVICA, 2015)
In this paper, we investigate some properties of pluriharmonic mappings defined in the unit ball. First, we discuss the relationship between the univalence of pluriharmonic mappings and linearly connected domains, and then we study Lipschitz-type spaces for pluriharmonic mappings.